HLA-E peptide repertoire and dimorphism-centerpieces in the adaptive NK cell puzzle? - Rölle, Alexander; Jäger, Dirk; Momburg, Frank (Frontiers in immunology, 2018)
Adaptive Natural Killer (NK) cells, a heterogenous subpopulation of human NK cells with a unique phenotypic and functional signature, became arguably one of the central areas of interest in the field. While their existence seems closely associated with prior exposure to human cytomegalovirus (HCMV), many questions regarding their origin and regulation remain unanswered. However, a common denominator for the majority of adaptive NK cells is the expression of the activating heterodimeric receptor CD94/NKG2C that binds to HLA-E, a non-classical HLA molecule, that displays a comparably restricted expression pattern, very limited polymorphism and presents a distinct set of peptides. Recent studies suggest that - in analogy to T cell responses - peptides presented on HLA-E could play an unexpectedly decisive role for the biology of adaptive NK cells. Here we discuss how this perspective on the CD94/NKG2C-HLA-E axis aligns with the existing literature and speculate about possible translational implications.